Qualitative analysis about best practices and project management tools in intralogistics (Nexo Revista Científica, 2024)
Project management in automotive manufacturing is crucial due to the dynamism in updating operating models and high investment in the supply chain and logistics. This article presents a systematic literature review of 134 articles (2011-2023) from four relevant databases (IEEE, ScienceDirect, Scopus, Taylor & Francis) with the purpose of exploring the best practices in project management applied in intralogistics activities. Analyzing aspects such as country, management methods and techniques, solution levels in internal logistics projects, business line, among other items. The findings will identify opportunities that contribute to academic indicators and the generation of proposals in the automotive industry in Mexico, focused on the fulfillment of projects and management according to their context.